2014
DOI: 10.1111/jsm.12430
|View full text |Cite
|
Sign up to set email alerts
|

Gender-Specificity of Solitary and Dyadic Sexual Desire among Gynephilic and Androphilic Women and Men

Abstract: Introduction Incentive motivation theory proposes that sexual desire emerges from sexual arousal, and is triggered by sexually competent stimuli. Research demonstrates gender and sexual orientation differences in the features that contribute to the competency of sexual stimuli. Men's and gynephilic women's genital arousal tends to be gender-specific with preferred gender eliciting significantly greater genital arousal than nonpreferred gender. In contrast, stimuli depicting preferred and nonp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
13
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
8
2

Relationship

1
9

Authors

Journals

citations
Cited by 36 publications
(13 citation statements)
references
References 80 publications
0
13
0
Order By: Relevance
“…Given findings showing greater fluidity in heterosexual women’s behavioral responses to sex-related stimuli than is evident in homosexual women, heterosexual men, or homosexual men (Chivers et al 2015; Dawson and Chivers, 2014), also group differences in the neural correlates of sexual preference might exist. However, there is also evidence for gender-specific genital and subjective responses in heterosexual women (Spape et al, 2014).…”
Section: Discussionmentioning
confidence: 99%
“…Given findings showing greater fluidity in heterosexual women’s behavioral responses to sex-related stimuli than is evident in homosexual women, heterosexual men, or homosexual men (Chivers et al 2015; Dawson and Chivers, 2014), also group differences in the neural correlates of sexual preference might exist. However, there is also evidence for gender-specific genital and subjective responses in heterosexual women (Spape et al, 2014).…”
Section: Discussionmentioning
confidence: 99%
“…Toates [ 62 ] proposed that sexual stimuli become incentivized through positive experiences and that the motivational value of incentives is amplified if accompanied by sexual arousal. Positive experiences such as genital vasocongestion and accompanying pleasurable sensations, particularly in the absence of negative affect to female sexual stimuli [ 5 ], could therefore incentivize nonpreferred sexual stimuli among androphilic women [ 63 ]. Multiple opportunities exist for further incentivization of same-gender sexuality beyond direct sexual contact with women, such as sexual fantasy with or without sexual activity (solitary or partnered) and consumption of sexual media.…”
Section: Discussionmentioning
confidence: 99%
“…Studies on arousal provided evidence that, while men demonstrated genital arousal primarily to female or male sexual stimuli (based on their sexual orientation), women exhibit genital arousal to both male and female sexual stimuli regardless of their orientation [44,47]. Dawson and Chivers [48] reported the presence of a higher level of nonspecific gender pattern of arousal in androphilic women, both in solitary and dyadic desire rather than gynephilic women.…”
Section: Sexual Fluiditymentioning
confidence: 99%